HUBUNGAN EFIKASI DIRI DENGAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS V SD INPRES 5/81 LEMOAPE KECAMATAN PALAKKA KABUPATEN BONE - Putri, Eliana; Kadir, Abd; Asriadi (MACCA : Science-Edu Journal, 2025)
This study is a type of correlational quantitative research that aims to find out whether or not there is a significant relationship between self-efficacy and mathematics learning motivation of grade V students of SD Inpres 5/81 Lemoape, Palakka District, Bone Regency. The population in the study is all grade V students using a sampling technique, namely a saturated sample of 36 students. The data collection technique was carried out using a questionnaire. The questionnaire used has gone through validity and reliability tests. The validity test used the SPSS version 25 program using a = 5% = 0.05 significance level and the r-valueof the table was 0.5324, while the reliability testing method used was to see the value of Cronbach's Alpha, namely the results of the self-efficacy test were at a value of 0.775 and the motivation to learn mathematics was at a value of 0.821. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistics, it was shown that self-efficacy obtained an average of 64.33 in the medium category and the motivation to learn mathematics obtained an average of 61.97 in the medium category. Based on the results of infernal statistical analysis, it shows that the rcalculation > rtable (0.655 > 0.3291) is at a significance level of 5%. Thus H1 is accepted and H0 is rejected. From the results of the study, it can be concluded that there is a significant relationship between self-efficacy and motivation to learn mathematics of grade V students of SD Inpres 5/81 Lemoape, Palakka District, Bone Regency which is categorized as strong in the interval of 0.60 – 0.799.